PERLINDUNGAN HAK CIPTA DIGITAL SEBAGAI BENTUK IMPLEMENTASI PENGEMBANGAN KEKAYAAN INTELEKTUAL PADA SISTEM ELEKTRONIK - Ranti Fauza Mayana; Tisni Santika; Zahra Cintana (Refleksi Hukum: Jurnal Ilmu Hukum, 2024)
The actualization of Intellectual Property Development in the Copyright regime, a derivative work through electronic media, must be balanced with extra protection outside the legal protection of Copyright regulated in the national Copyright Law. Improving the quality of digital Copyright protection is necessary, considering that digital Copyright objects have increasingly transformed into various new forms, followed by the possibility of digital Copyright Infringements. The resolution of problems related to the legal issues of digital copyright infringement needs to be carried out through a legal and technological approach, which will be discussed through this research in several forms of legal protection efforts and non-legal protection as complementary protection.